High-Temperature Oxidation and Microstructural Changes of Al0.75CoCrFeNi High-Entropy Alloy at 900 and 1100 °C - Akhmad Ardian Korda; Mohamad Ali Akbar; Fadhli Muhammad; Tria Laksana Achmad; Budi Prawara; Djoko Hadi Prajitno; Bagus Hayatul Jihad; Muhamad Hananuputra Setianto; Eddy Agus Basuki (Metals, 2023)
The development of high-entropy alloys (HEAs) for high-temperature applications has been driven by the limitation of nickel-based superalloys in achieving optimal efficiency at higher temperatures for higher efficiency in power generation engines. The alloys must have high oxidation resistance and microstructural stability at high temperatures. Relatively equimolar multi elements involved in HEAs produce microstructure containing a single solid solution or multiphase that improves the mechanical properties and oxidation resistance resulting from sluggish diffusion and core effects. In this study, the oxidation behavior and microstructural changes of Al0.75CoCrFeNi HEA at 900, 1000, and 1100 °C in air atmosphere were investigated. Based on the XRD and SEM-EDS analysis, the mechanism of oxide scale formation and microstructural changes of the substrate are proposed. The results show that the oxidation behavior of the alloy follows a logarithmic rate law. Different oxide compounds of CoO, NiO, Cr2O3, and CrO3, θ-Al2O3, α-Al2O3, and Ni(Cr,Al)2O4 with semicontinuous oxides of Al2O3 with Cr2O3 subscale and an oxide mixture consisting of spinel of Ni(Cr,Al)2O4 and Co(Cr,Al)2O4 were found. During oxidation, Widmanstätten of FCC-A1 and BCC-B2/A2 phases in the substrate have changed. Spheroidization of B2 and a reduction in volume fraction decrease the hardness of the substrates.